TINJAUAN MEKANISME PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DI PEMERINTAHAN KOTA CIMAHI - Paryati, Retno; Saputri, Dinda (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2023)
Abstract This study aims to determine how the mechanism of collecting Fees on Acquisition of Land and Building Rights in Cimahi City Government. The research methodology in this study uses a descriptive method with a qualitative approach. This research data collection technique was carried out by observation, interviews and literature studies. The results show that the mechanism of BPHTB collection in Cimahi city government is set in the regulation of the mayor of Cimahi No. 6 of 2015 on procedures for collecting local taxes paid by taxpayers themselves, which was last amended by the regulation of the mayor of Cimahi No. 53 of 2016. BPHTB collection at Cimahi City Government is carried out online. Especially for the purposes of Wills and Inheritance Grants, BPHTB collection is carried out offline. The implementation of coordination between authorized officials includes registration of land and/or building rights, making and signing of Land Deeds, validation status and at the time of making BPHTB online there is a Memorandum of Understanding (MOU) regarding land registration. There are obstacles in the BPHTB collection mechanism in the Cimahi City Government, namely PPAT/PPATs often do not check files before making the booking process.